2023
DOI: 10.1111/hel.13039
|View full text |Cite
|
Sign up to set email alerts
|

Vonoprazan and amoxicillin dual therapy as the first‐line treatment of Helicobacter pylori infection: A systematic review and meta‐analysis

Ren‐Chun Du,
Yu‐Xin Hu,
Yaobin Ouyang
et al.

Abstract: BackgroundRecent clinical trials have evaluated the efficacy of vonoprazan‐amoxicillin (VA) dual therapy as the first‐line treatment for Helicobacter pylori infection in different regions with inconsistent results reported. In this systematic review and meta‐analysis, we aimed to evaluate the efficacy of VA dual therapy compared to the currently recommended therapy for eradicating H. pylori.Materials and MethodsA comprehensive search of the PubMed, Cochrane, and Embase databases was performed using the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Body size (body surface area and BMI) reduces the effectiveness of P-CABs, whereas the presence and severity of corpus gastritis improve treatment outcomes [66]. Overall, highly effective dual therapy requires excellent control of gastric pH, suggesting that optimization will often be required for different populations (i.e., one size may not fit all) [35,46,53,[67][68][69][70][71][72][73][74][75][76].…”
Section: The Future Of H Pylori Therapy: Vonoprazan Dual Therapymentioning
confidence: 99%
“…Body size (body surface area and BMI) reduces the effectiveness of P-CABs, whereas the presence and severity of corpus gastritis improve treatment outcomes [66]. Overall, highly effective dual therapy requires excellent control of gastric pH, suggesting that optimization will often be required for different populations (i.e., one size may not fit all) [35,46,53,[67][68][69][70][71][72][73][74][75][76].…”
Section: The Future Of H Pylori Therapy: Vonoprazan Dual Therapymentioning
confidence: 99%
“…associated with higher H. pylori eradication rates in amoxicillincontaining dual therapy. 9 Inspired by the enhanced efficacy observed in AMX-containing dual therapy, it was hypothesised that tetracycline's antimicrobial effect might be more stable and exhibit better bioavailability in the gastric cavity under the higher intragastric pH value produced by vonoprazan. The results of this study demonstrated that the efficacy of VT dual therapy was non-inferior to that of classical BQT, as determined by ITT, mITT and PP analyses.…”
Section: Helicobacter Pylorimentioning
confidence: 99%